1990
DOI: 10.1139/f90-099
|View full text |Cite
|
Sign up to set email alerts
|

Increased Juvenile Salmonid Growth by Whole-River Fertilization

Abstract: 1990. increased juvenile salmonid growth by wholeriver fertilization. Can. ). Fish. Aquat. Sci. 47: 862-872.Nutrient concentrations, periphyton standing crop and size of steelhead trout (8ncsrhynehus mykiss) and coho salmon (8. kisuteh) fry increased after the fertilization of a nutrient-deficient stream with inorganic phosphorus (P) and nitrogen (N). Wh~le-river fertilimation of the Keogh River, British Columbia, during 4983-86 to increase summer average nutrient csncentrations f r~r n <1 p, g POL-' and 25 pg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 42 publications
3
94
0
Order By: Relevance
“…Investigators also have reported significant increases in salmon production following nutrient addition in nutrient-depleted lakes and streams in British Columbia, Idaho, and Alaska (Johnson et al 1990, Stockner 2003. The effects of reduced nutrient availability and biological production on naturally reproducing anadromous Pacific salmon populations have been described extensively in the literature (Schindler et al 2003, Wipfli et al 2003, Janetski et al 2009), but anthropogenic oligotrophication also has reduced nutrient availability and biological production in rivers and lakes beyond the extent of marine-derived nutrient contributions .…”
mentioning
confidence: 99%
“…Investigators also have reported significant increases in salmon production following nutrient addition in nutrient-depleted lakes and streams in British Columbia, Idaho, and Alaska (Johnson et al 1990, Stockner 2003. The effects of reduced nutrient availability and biological production on naturally reproducing anadromous Pacific salmon populations have been described extensively in the literature (Schindler et al 2003, Wipfli et al 2003, Janetski et al 2009), but anthropogenic oligotrophication also has reduced nutrient availability and biological production in rivers and lakes beyond the extent of marine-derived nutrient contributions .…”
mentioning
confidence: 99%
“…Whether through the application of liquid agricultural fertilizer, pelletized forms of slow release fertilizer, or even from the addition of sucrose as a source of nutrients, nutrient addition has often led to large increases in stream periphyton and benthic invertebrate abundance (Warren et al 1964;Johnston et al 1990;Slavik et al 2004). Effects on the abundance of salmonids have been detected in the form of increased growth and abundance in some instances (Ward et al 2003), but not others (Wipfli et al 2010;Harvey and Wilzbach 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In oligotrophic aquatic habitats, the addition of nutrients has produced dramatic increases in primary production as well as their secondary consumers (Johnston et al 1990;Slavik et al 2004). While increases in salmonid fish production have been observed in fertilized lakes (Stockner and MacIsaac 1996), the effect on salmonid production in streams has been equivocal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The watershed, more fully described in Ward and Slaney (1979), Irvine and Ward (1989), and Johnston et al (1990), is in the coastal western hemlock biogeoclimatic zone, with mean annual discharge of 5.3 m 3 ·s -1 and an estimated winter maximum of 254 m 3 ·s -1 . The Keogh River fish fence is situated 300 m upstream from the river mouth, at approximately the high tide mark, and has permitted virtually complete enumeration of downstream-migrant fish during spring, and accurate estimates of the steelhead spawners migrating upstream, since 1976.…”
Section: Methodsmentioning
confidence: 99%